Synthesis of Colloidal Silver Nanoparticles in Various Liquid Media Using Pulse Laser Ablation Method and Its Antibacterial Properties - Syifa Avicenna; Iis Nurhasanah; Ali Khumaeni (Universitas Gadjah Mada, 2021)
The silver nanoparticles (AgNPs) have been applied as an antibacterial agent in consumer products, cosmetics, and food industries. In this present work, AgNPs were synthesized in various mediums of polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), and chitosan using the pulse laser ablation synthesis method. Experimentally, a pulse Nd:YAG laser beam (1064 nm, 7 ns, 30 mJ) was directed using a silver mirror and focused using a quartz lens with a focal length of 30 mm on a silver metal plate placed in a petri dish containing liquid mediums for 120 min to produce colloidal silver nanoparticles. The results certified that All AgNPs have a spherical shape with polydisperse size in all media, including PVP, PEG, and chitosan. The smallest AgNPs have been produced in PVP medium with an averaged smallest size of 11.62 nm. Based on this result, PVP is the preferred medium to produce AgNPs with the smallest size and good stability. The produced silver nanoparticles have been successfully employed as an antibacterial agent, which is experimentally demonstrated by using Escherichia coli and Staphylococcus aureus. The result certified that the produced silver nanoparticles could effectively kill the bacteria with a killing percentage of 99.6 to 100%.